Pengaruh Mobilisisasi Dini Terhadap Penurunan Rasa Nyeri pada Pasien Post Sectio Caesarea dengan Spinal Anestesi di RSUD Padang Panjang - Yusuf, Gilang Navaza; Devita, Hendri; Andriyan, Aric Frendi; Pasalina, Putri Engla (STIKES Ngesti Waluyo, 2024)
Post-section caesarea pain under spinal anesthesia can inhibit the patient's activities and is one of the reasons the patient does not want to move. One of the non-pharmacological therapies used to reduce pain management is early mobilization. The purpose of this study was to determine the effect of early mobilization on reducing pain in post-section caesarea patients with spinal anesthesia at Padang Panjang Hospital in 2022. Data collection was carried out at Padang Panjang Hospital in January-February 2023. This type of research is quantitative research using the pre-experimental method with the design of a one-group pre-test and post-test. The sample is 35 respondents, and the sampling technique is purposive sampling. The research instrument uses the NRS Scale. The results showed that most of the respondents were aged 25-35 years, namely 24 people (68.6%), and mostly were high school and bachelor graduates, as many as 15 people each (42.9%). Before early mobilization, most patients experienced moderate pain, namely 29 people (82.9%), and after mobilization, most patients experienced mild pain, namely 29 people (82.9%) at Padang Panjang Hospital. There was a reduction in pain after early mobilization at Padang Panjang Hospital (p=0,000). The study concludes that early mobilization has an effect on reducing pain in post-sectio caesarea patients with spinal anesthesia at Padang Panjang Hospital in 2022. It is recommended for health workers to socialize or implement early mobilization in post-sectio caesarea patients to reduce pain levels in patients.